Bio-catalytic asymmetric synthesis of β-adrenergic receptor blocker precursor: (R)-2-bromo-1-(naphthalen-2-yl)ethanol - Tasdemir, Volkan; Kalay, Erbay; Dertli, Enes; Sahin, Engin (TAYLOR & FRANCIS LTD, 2020)
Aromatic alpha-halohydrins, particularly 2-haloethanols as significant precursor of drugs, can easily be converted to chiral beta-adrenergic receptor blockers. Eight strains of Lactobacillus curvatus were tested as biocatalysts for asymmetric reduction of 2-bromo-1-(naphthalen-2-yl)ethanone 1 to 2-bromo-1- (naphthalen-2-yl) ethanol 2. The parameters of the bioreduction were optimized using L. curvatus N4, the best biocatalyst found. As a result, (R)-2-bromo-1-(naphthalen-2-yl)ethanol 2, which can be beta-adrenergic receptor blocker precursor, was produced for the first time in high yield and enantiomerically pure form using biocatalysts. Moreover, the gram scale synthesis was performed and 7.54 g of (R)-2 was synthesized as enantiopure form (enantiomeric excess >99%) in 48 h. The important advantages of this process are that it produces of (R)-2 for the first time in enantiopure form, in excellent yield and under environmentally friendly and moderate reaction conditions. This system is of the potential to be applied at a commercial scale.
Keywords: Chiral 2-haloethanols; biocatalysts; asymmetric reduction; (R)-2-bromo-1-(naphthalen-2-yl)ethanol; Lactobacillus curvatus; BETA(2)-ADRENOCEPTOR AGONISTS; TRANSFER HYDROGENATION; CARBONYL REDUCTASE; KETONES; HYDRATION; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology